Cutaneous factitia in elderly patients: alarm signal for psychiatric disorders - Chiriac A (Dove Medical Press, 2014)
Anca Chiriac,1 Liliana Foia,2 Cristina Birsan,1 Ancuta Goriuc,2 Caius Solovan3 1Department of Dermatology, Nicolina Medical Center, Iaşi, Romania; 2Surgical Department, Grigore T Popa University of Medicine and Pharmacy, Iaşi, Romania; 3Department of Dermatology, Victor Babeş University of Medicine and Pharmacy, Timişoara, Romania Background: The factitious disorders, more commonly known in daily practice as pathomimia, are expressed in dermatology units by skin lesions induced voluntarily by the patient, in order to draw attention of the medical staff and/or the family members. The disorder is often challenging to diagnose and even more difficult to document in front of the patient or relatives. It represents a challenge for the physician, and any attempt at treatment may be followed by recurrence of the self-mutilation. This paper describes two cases of pathomimia diagnosed by dermatologists and treated in a psychiatry unit, highlighting the importance of collaboration in these situations. Patients and methods: Two case reports, describing old female patients with pathomimia, hospitalized in a department of dermatology for bizarre skin lesions. Results: The first case was a 77-year-old female with unknown psychiatric problems and atrophic skin lesions on the face, self-induced for many months, with multiple hospitalizations in dermatology units, with no response to different therapeutic patterns, and full recovery after psychiatric treatment for a major depressive syndrome. The second case was a 61-year-old female patient with disseminated atrophic scars on the face, trunk, and limbs. She raised our interest because of possible psychiatric issues, as she had attempted to commit suicide. The prescription of antidepressants led to a significant clinical improvement. Conclusion: These cases indicate that a real psychiatric disease may be recorded in patients suffering from pathomimia. Therefore, complete psychiatric evaluation in order to choose the proper therapy is mandatory for all these cases. Dermatologists and all physicians who take care of old patients must recognize the disorder in order to provide optimum care for this chronic condition. We emphasize therefore the importance of psychiatric evaluation and treatment to avoid the major risk of suicide. Skin lesions must be regarded as an alarm signal in critical cases, especially in senior people. Keywords: pathomimia, elderly, psychiatric disorders